IMPLEMENTASI METODE TOPSIS DALAM PENENTUAN CALON TRANSMIGRAN DI INDONESIA - Ngemba, Hajra Rasmita; Angreni, Dwi Shinta; Winarta, Ardhiansyah; Hendra, Syaiful; A Djufri, Isdar (ScientiCO : Computer Science and Informatics Journal, 2020)
The population in Indonesia is growing, causing population density in an area. One of the impacts of population density in an area is that it causes job opportunities in that area to become smaller, so that the unemployment rate increases. To overcome this problem, the government moved or spread the population from a densely populated area to another area with a small population with the aim of improving the economy and opening up agricultural land in the region. However, problems in the field include the limited quota of transmigrant participants from the central government. So it makes it difficult to choose or make decisions to determine potential transmigration participants. This study aims to assist the government in making decisions to determine suitable transmigrant candidates using the TOPSIS(Technique for Order Preference By Similiarity To Ideal Solution) method. Application development using the prototype method with blackbox testing. Decision Support System Applications Determining prospective transmigrants can assist users (government) in determining eligible transmigrant candidates with the criteria desired by the government.